2014
DOI: 10.7150/ijms.9343
|View full text |Cite
|
Sign up to set email alerts
|

A Novel PCR-Based Approach to Discover miRNA Target Genes

Abstract: MiRNAs are potent regulators of gene expression, and most miRNAs have from several to several thousands of gene targets. Validating the numerous gene targets of a given miRNA remains challenging despite the existence of various tools and databases that predict candidate gene-miRNA pairs. In the present study, we present a high-throughput but flexible method that applies a PCR-based application to simulate the binding of miRNAs to their gene targets. Using hsa-miR-377 as an illustrative example, our method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…To explore the mechanism by which miR-221-3p protects hippocampal neurons from sevoflurane induced nerve injury, we predicted and discovered that CDKN1B was the target gene of miR-221-3p. MiRNA participates in biological processes in human organism mainly by regulating the expression of its target genes [30,31]. Dong-Mei Wu et al shown that miR-142-3p can partially promote the neuronal cell cycle and inhibit cell apoptosis by inhibiting CDKN1B and TIMP3 expressions [32].…”
Section: Discussionmentioning
confidence: 99%
“…To explore the mechanism by which miR-221-3p protects hippocampal neurons from sevoflurane induced nerve injury, we predicted and discovered that CDKN1B was the target gene of miR-221-3p. MiRNA participates in biological processes in human organism mainly by regulating the expression of its target genes [30,31]. Dong-Mei Wu et al shown that miR-142-3p can partially promote the neuronal cell cycle and inhibit cell apoptosis by inhibiting CDKN1B and TIMP3 expressions [32].…”
Section: Discussionmentioning
confidence: 99%
“…The miR-377 appears as an important aging regulator by regulating, among others, superoxide dismutase 2 enzyme (SOD-2) 13,14 . SOD is the body's main antioxidant, which catalyzes the conversion of superoxide radicals to hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%